Enflurane 마취로 위절제술을 받는 위암환자의 Digoxin 약동학 - 이수일; Soo Il Lee; 김형호; Hyung Ho Kim; 김병진; Byung Jin Kim; 이도경; Do Kyung Lee; 백창열; Chang Youl Baik; 이종환; Jong Hwan Lee (Korean journal of anesthesiology, 2002)
KCI Citation Count: 0